Perbedaan Proses Pengadaan Barang Dan Jasa Metode Konvensional Dengan Menggunakan Jurnal Mekari Di PT. Sarana Remaja Mandiri - Lathifia Qolbina; Seconddina Wahyu Riya; Ramadhan Azzahdewa Devangga; Alfian Febriansyah Muttaqin; Dika Ayu Safitri (International Forum of Researchers and Lecturers, 2024)
Procurement of Goods and Services at PT. Sarana Remaja Mandiri still use conventional systems. By using the Mekari Journal, as a procurement process in the company, it will have a significant impact on developing more efficient procurement. Organizations across all industries rely on Procurement Management expertise to source and manage relationships with external suppliers, ensuring these needed goods are obtained at the best cost. This aims to determine differences in procurement of goods and services at PT. Sarana Remaja Mandiri. The method used is the Mekari Journal, which makes it easier to document the documentation process for procurement of goods and services at PT. Sarana Remaja Mandiri. The Mekari journal will record the entire PO process that has been issued, delivery status, and payment status. Mekari Journal makes it easier for related parties in the company to access the progress of the goods and services procurement process. After analyzing and discussing the problem, the author comes to the conclusion that in the PO (purchase order) process, Jurnal Mekari helps in the efficiency process because by using this software, the procurement party only needs to enter related data such as supplier name, PO number, item name, number of items. , etc. By filling in the data in the Mekari Journal in the Purchase Order section, a PO will automatically be issued along with a template. So, companies don't need to create templates for PO documents.